Fruit dispersal of two dipterocarp species in a Malaysian rain forest - Osada, Noriyuki; Takeda, Hiroshi; Furukawa, Akio; Awang, Muhamad (Cambridge University Press, 2001)
Seed dispersal is the predominant mobile stage for sessile plants, and critically affects the distribution patterns of the species (Nathan & Muller-Landau 2000). Thus, seed dispersal patterns are important in understanding the population dynamics of the species.